PENGGUNAAN MEDIA SOSIAL TIKTOK PADA WAKTU YANG BERBEDA DALAM SEHARI TERHADAP MOTIVASI PENGGUNA DAN EFEKTIVITAS IKLAN TIKTOK - Ryan Fazriansyah; Willy Arafah (EBID: Ekonomi Bisnis Digital, 2026)
This study aims to analyze the effect of TikTok social media usage at different times of the day on user motivation and TikTok advertising effectiveness. The research variables include TikTok on Mobile Most Intense Use During the Day vs Evening, Motivation to Use TikTok: Seek Information, Seek Entertainment, Seek Friends, Seek Support, and Advertising Outcomes: Brand Recall, Click on Ads, Act on Ads, Purchase. This study used a quantitative approach with data collected through questionnaires distributed to 105 Generation Z respondents aged 18–27 years who actively use TikTok. The sampling technique used purposive sampling, and the data were analyzed using Structural Equation Modeling (SEM) with AMOS software. The results showed that all hypotheses were supported. TikTok usage during the day and evening positively affected users’ motivation to seek information, entertainment, friends, and social support. In addition, users’ motivation to use TikTok also positively influenced TikTok advertising effectiveness. These findings indicate that the higher the intensity of TikTok usage, the higher the effectiveness of advertisements received by users.